Pelatihan Pembuatan Keripik Jahe untuk Warga Desa Gunung Sari Way Kanan Lampung - Feerzet Achmad; Ay Ahmad; Muhammad Abdul Muhdi Bindar; Ridwan Pratama Yudha; Suhartono Suhartono; Suharto Suharto (Jurnal Ilmiah Pangabdhi, 2022)
Ginger (Zingiber officinale Rosc) is efficacious as a cooking spice and traditional medicine. Lampung Province produces ginger as much as 2,351 tons and especially in Way Kanan Regency, 234 tons of ginger is produced in 2021. This large production of ginger is an opportunity for residents to process ginger into healthy snacks such as ginger chips. Based on the potential, Institut Teknologi Sumatera students conducted ginger chip-making training as a community service. This training targeted residents which are part of a community organization in Gunung Sari Village, Rebang Tangkas District, Way Kanan Regency. Through this training, residents can increase their knowledge and understanding of the efficacy, benefits, processing, and manufacture of ginger chips. These ginger chips are a healthy snack and very suitable for consumption during the Covid-19 pandemic. This is evidenced by the results of the evaluation which increased significantly after the ginger chip processing training.